In vitro demonstration and in planta characterization of a condensed, reverse TCA (crTCA) cycle - Wilson, Nathan; Smith-Moore, Caroline; Xu, Yuan; Edwards, Brianne; La Hovary, Christophe; Li, Kai; Aslett, Denise; Ji, Mikyoung; Lin, Xuli; Vintila, Simina; Kleiner, Manuel; Xie, Deyu; et al. (Frontiers in Plant Science, 2025)
IntroductionPlants employ the Calvin-Benson cycle (CBC) to fix atmospheric CO2 for the production of biomass. The flux of carbon through the CBC is limited by the activity and selectivity of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (RuBisCO). Alternative CO2 fixation pathways that do not use RuBisCO to fix CO2 have evolved in some anaerobic, autotrophic microorganisms.MethodsRather than modifying existing routes of carbon metabolism in plants, we have developed a synthetic carbon fixation cycle that does not exist in nature but is inspired by metabolisms of bacterial autotrophs. In this work, we build and characterize a condensed, reverse tricarboxylic acid (crTCA) cycle in vitro and in planta.ResultsWe demonstrate that a simple, synthetic cycle can be used to fix carbon in vitro under aerobic and mesophilic conditions and that these enzymes retain activity whenexpressed transiently in planta. We then evaluate stable transgenic lines of Camelina sativa that have both phenotypic and physiologic changes. Transgenic C. sativa are shorter than controls with increased rates of photosynthetic CO2 assimilation and changes in photorespiratory metabolism.DiscussionThis first iteration of a build-test-learn phase of the crTCA cycle provides promising evidence that this pathway can be used to increase photosynthetic capacity in plants.